Evaluation of driving comfort among driver; MYVI 1.3 L (MANUAL) / Mohd Razin Azim Abd Rahman - Abd Rahman, Mohd Razin Azim (2010)
Cars drivers are highly exposed to fatigue and work related injuries when driving in the long time especially in manual cars. Car drivers are common sufferers of musculoskeletal disorders, frequently suffering from pain symptoms particularly in the neck, shoulder and lower back. A high percentage of this problem is due to the wrong driving posture resulting from inappropriate seat design. This incorrect and poor design is owing to the insufficient and obsolete anthropometrical data which has been used for decades for arranging and positioning components in the driver environment. The steering wheel positions as well as the pedal or floor locations were hypothesized to be highly associated to the driver's selected posture and the comfort of drivers. The effect of the seat posture selection and related comfort assessments will make the driver feel uncomfortable while driving. An experiment has been conduct using PERODUA MYVI 1.3L (MANUAL) in the real road condition. Five subjects have been taken to take part in this experiment. The subject will ask to set their seat position in the car, so that there will feel comfortable during driving. In this experiment, only lower part of the body to be considered and electromyography is use to detect muscle at the leg of drivers. The subject must drive about 90 minute and the data were taken from the electromyography graph. From this graph, it will show the fatigue occur when the subject driving.